2011
DOI: 10.1159/000323867
|View full text |Cite
|
Sign up to set email alerts
|

The Montreal Cognitive Assessment and the Mini-Mental State Examination as Screening Instruments for Cognitive Impairment: Item Analyses and Threshold Scores

Abstract: Aims: To perform an item analysis of the Montreal Cognitive Assessment (MoCA) versus the Mini-Mental State Examination (MMSE) in the prediction of cognitive impairment, and to examine the characteristics of different MoCA threshold scores. Methods: 135 subjects enrolled in a longitudinal clinicopathologic study were administered the MoCA by a single physician and the MMSE by a trained research assistant. Subjects were classified as cognitively impaired or cognitively normal based on independent neuropsychologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
162
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(180 citation statements)
references
References 31 publications
13
162
2
3
Order By: Relevance
“…To provide further evidence in a related participant group and to increase our sample size, we also administered the task to older adults at risk for MCI, on the assumption that the integrity of the PRC would already be compromised in the earliest stages of the disorder (e.g., Du et al, 2001;Loewenstein et al, 2009;Schmidt-Wilcke et al, 2009). We identified these individuals at risk for MCI based on the Montreal Cognitive Assessment (MoCA), a brief standardized neuropsychological measure shown to be extremely sensitive in distinguishing controls from MCI patients (Nasreddine et al, 2005;Damian et al, 2011). Consistent with the cut-off scores provided by the developers of the MoCA (Nasreddine et al, 2005), we included older adults who scored below 26/30 on the MoCA as at risk for MCI, and older adults who scored 26/ 30 or above as a healthy control group.…”
Section: Introductionmentioning
confidence: 99%
“…To provide further evidence in a related participant group and to increase our sample size, we also administered the task to older adults at risk for MCI, on the assumption that the integrity of the PRC would already be compromised in the earliest stages of the disorder (e.g., Du et al, 2001;Loewenstein et al, 2009;Schmidt-Wilcke et al, 2009). We identified these individuals at risk for MCI based on the Montreal Cognitive Assessment (MoCA), a brief standardized neuropsychological measure shown to be extremely sensitive in distinguishing controls from MCI patients (Nasreddine et al, 2005;Damian et al, 2011). Consistent with the cut-off scores provided by the developers of the MoCA (Nasreddine et al, 2005), we included older adults who scored below 26/30 on the MoCA as at risk for MCI, and older adults who scored 26/ 30 or above as a healthy control group.…”
Section: Introductionmentioning
confidence: 99%
“…Different psychometric tests have been proposed for screening purposes [2,3]. The Mini Mental State Examination (MMSE) is the most popular and is widely used to follow cognitive decline along with time as well as to monitor the effects of drug treatments [4].…”
Section: Introductionmentioning
confidence: 99%
“…The American Academy of Neurology guidelines suggested to use the Mini-Mental Status Examination [66], and the Memory Impairment Screen (MIS) [67]. In recent times, the Montreal Cognitive Assessment (MoCA) was developed as a tool to screen patients in who has been hypothesized a mild cognitive decline and usually performed in the normal range on the MMSE [68,69]. Studies have shown that MoCa is sensitive for the mild stages of AD dementia, whereas MMSE is superior for more advanced stages with the functional impairment.…”
Section: Mci-core Clinical Criteriamentioning
confidence: 99%